Medroxyprogesterone acetate in homemade intravaginal devices for estrus synchronization in hair ewes: Evaluation of efficacy, adverse effects and comparison with a commercial device in Costa Rican herds. - González, Silvia (2017)
The goal of our study was to determine the pharmacological efficacy and adverse effects of a homemade intravaginal device containing medroxyprogesterone acetate for estrus synchronization in hair ewes. A total of 78 adult, multiparous, cycling females were included in the two-phase experiment. During the first phase 18 ewes were included, and the efficacy and adverse effects of the homemade device were evaluated. In the second phase 60 ewes were aleatory assigned into two experimental groups: (G1) homemade intravaginal device (n-30), and (G2) commercial device (n-30) with the goal of comparing the estrus synchronization rate and conception rate among groups when using natural mating. The protocol consisted of 12-days treatment with 60mg of medroxyprogesterone acetate (MAP) by using the intravaginal device, followed by 200 UI eCG and 5 mg dinoprost tromethamine injection on day 12. A total of 13 males were tested by complete andrological evaluation, 8 were included as satisfactory males for the experiments. During both phases no signs of estrus were observed during the treatment with MAP, and 100% showed estrous signs 48 hours after device withdrawal. Adverse effects observed in the first part included: Mild vaginitis in all ewes, 3 females presented adherences, 2 showed fibrinogen increase at day 12, and a general lower leucocyte count after treatment was observed. In the second phase, no differences in estrus synchronization was observed among groups, and conception rates were 80.0% and 76.7% for G1 and G2 respectively. We conclude that the homemade intravaginal device is as effective as a commercial one for estrus synchronization, which allows obtaining high pregnancy rates in hairy sheep in Costa Rica.